PERANCANGAN USER INTERFACE DAN USER EXPERIENCE HALAMAN WEBSITE PROGRAM STUDI DESAIN KOMUNIKASI VISUAL UNIVERSITAS NEGERI PADANG - ABDUL NASER, Dr. Syafwandi, M.Sn., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
In this instant digital era, Visual Communication Design major in Universitas Negeri Padang  (DKV UNP) still does not have a fast, complete, and easy information delivery medium. Whereas  in addition to students and teaching staff, outside groups such as school students and industry professional also need informations of DKV UNP. So information delivery medium for educational institution such as website, is needed.The DKV UNP website is designed with good UI / UX to have a good layout and flow, so users  will not confused and difficult to find the information needed. Website content is arranged in order and grouping based on the user's profession and information, so that users can easily get the  information. This website is expected to be a profile publication media and presentation DKV that can be used for media announcements to students and staffs, media information for  students, prospective students, and industry professional, as well as archive media for alumni.In the troubleshooting process, 5W + 1H analysis (what, who, where, when, why, how) is used to  find the solution of the problem. In compiling the information retrieval flow, an observation of  user behavior and desires is used, and the results of studies and observations are arranged in a simple layout and do not confuse users. To support the main media, applications, manual books, guide CDs, motion graphics, e-banners, Instagram account feeds, and T-shirts, are made.Keyword : Website, visual communication design, user interface, user experience